ANALYSIS OF FINANCIAL STATEMENTS TO MEASURE THE FINANCIAL PERFORMANCE OF THE COMPANY BEFORE AND DURING THE COVID-19 PANDEMIC IN PT. CLIPAN FINANCE INDONESIA TBK - abdul muttalib; Nasrullah Nasrullah; Liya Saputri (Jurnal Ilmu Manajemen Profitability, 2021)
This study aims to determine the Financial Performance Before and During the Covid-19 Pandemic at PT. Clipan Finance Indonesia Tbk. The research results in terms of leverage ratios, namely DAR (Debt to totalTotalt Ratio) and DER (Debt to totalTotalty Ratio) show how the Financial Performance of PT. ClipanClipce Indonesia Tbk did not experience a negative impact from the Covid-19 Pandemic because the ratio decreased from the time of the covid-19 pandemic (2020) compared to before the covid-19 pandemic which showed the company's liabilities were smaller than its assets and equity. In terms of profitability, namely ROA (Return On Assets), ROE (Return On Equity), NPM (Net Profit Margin) and BOPO, (Operational Expenses to Operational Income) it can be concluded that the Covid-19 Pandemic hurts the Financial Performance of PT. Clip FClip Indonesia Tbk due to decreased 3 ratios with increased operating expenses. In terms of liquidity, namely the Current Ratio and Net Working Capital to Total Assets, it can be concluded that the current ratio of PT Clipan Finance Indonesia Tbk has increased although it cannot be said to be good. While on the NWCA side, liquidity has decreased due to the impact of the covid-19 Pande mic pandemic the covid-19 pandemic